2020
DOI: 10.3389/fvets.2020.00200
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multiplex Real-Time PCR and PCR-Reverse Blot Hybridization Assays for the Direct and Rapid Detection of Porcine Circovirus Type 2 Genotypes

Abstract: Porcine circovirus type 2 (PCV2), the causative agent of porcine circovirus-associated diseases (PCVAD), poses a serious economic threat for the swine industry. Currently, PCV2 is classified into five major genotypes: PCV2a, PCV2b, PCV2c, PCV2d, and PCV2e. The aim of this study is to evaluate the performance of two commercially available methods, multiplex real-time PCR assay and PCR-reverse blot hybridization assay (REBA), for the rapid detection of PCV2 and direct identification of PCV2 genotypes from clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…The TBIRD qPCR master mix, which has high sensitivity, specificity, and cost-effectiveness, is usually used for the Single-CoCoMo assay [10,11,29,31,33,34,[41][42][43][44][45]. In addition, the TBIRD qPCR master mix has been used in several multiplex qPCR assays [46]. Contrary to our expectations, in this study, the use of TBIRD in the Liquid Dual-CoCoMo assay showed reduced measurement accuracy compared with the GeneAce-based Dual CoCoMo assay.…”
Section: Discussioncontrasting
confidence: 73%
“…The TBIRD qPCR master mix, which has high sensitivity, specificity, and cost-effectiveness, is usually used for the Single-CoCoMo assay [10,11,29,31,33,34,[41][42][43][44][45]. In addition, the TBIRD qPCR master mix has been used in several multiplex qPCR assays [46]. Contrary to our expectations, in this study, the use of TBIRD in the Liquid Dual-CoCoMo assay showed reduced measurement accuracy compared with the GeneAce-based Dual CoCoMo assay.…”
Section: Discussioncontrasting
confidence: 73%
“…To establish prevention and control strategies for PCV2, PCR assays are sensitive methods to detect viruses in animals [ 28 ]. Several different PCR-related methods have been employed, such as ddPCR [ 17 ], real-time PCR [ 12 14 18 ], and LAMP [ 15 16 ]. The ddPCR require an expensive thermocycler and are time-consuming and difficult to perform for inexperienced investigators.…”
Section: Discussionmentioning
confidence: 99%
“…PCV2 was primarily determined by the restriction fragment length polymorphism (RFLP) assay for genotype differentiation [ 10 ] or detected viral DNA in tissues through immunohistochemistry (IHC) [ 11 12 ] and/or in situ hybridization (ISH) [ 13 ]. PCR-based diagnostic methods were also proposed, including real-time PCR [ 12 ], multiplex real-time PCR [ 14 ], loop-mediated isothermal amplification (LAMP) PCR [ 15 16 ], droplet digital PCR (ddPCR) [ 17 ], and SYBR TaqMan-based PCR [ 18 ] assays. Furthermore, commercial kits or antigens detecting PCV2 antibodies based on enzyme-linked immunosorbent assay (ELISA) were also available [ 19 20 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The TaqMan-based quadruplex real-time PCR was able to differentiate four species of PCV strains in clinical samples, rapidly and simultaneously [ 228 ]. Recently, multiplex real-time PCR has been developed, which is rapid, sensitive, efficient, and highly specific, allowing the detection and discrimination of different PCVs from clinical samples and even comparison of different genotypes of a particular species without requiring any specialized laboratory equipment [ 229 , 230 ]. Droplet digital PCR (ddPCR) is another novel PCR technology used for the detection of PCV2 and PCV3 with greater analytical sensitivity than TaqMan real-time PCR [ 231 , 232 ].…”
Section: Factors Associated With Clinical Manifestation Of Pcv-associ...mentioning
confidence: 99%